Multi-element ultrahigh-temperature ceramic and C / C structure function integrated gradient composite material and preparation method thereof

By depositing thermal solution of the carbon fiber prefabrication surface and degradation of ceramic matrix, the integrated gradient composite material of multiple ultra -high temperature ceramics and C/C structure function is prepared, and the ceramic base composite material is solved The lack of ablation resistance has realized the integration of structural carrying and anti -ablation function.

CN119350049APending Publication Date: 2025-01-24AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411549046.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing ceramic matrix composite materials are difficult to take into account good high temperature mechanics and oxidation and ablation resistance, and lack the function of integrating structural bearing and ablation resistance.

Method used

The chemical gas sedimentation method is used to deposit thermal carbon interface layer of the fiber surface of the carbon fiber pre -pre -dwelling body, forming a low -density C/C substrate, and degrades through multiple rounds of ceramic matrix to form a diverse ultra -high temperature ceramics and the C/C structure. Functional integrated gradient composite material.

Benefits of technology

The prepared composite materials have both lightweight, good carrying capacity and antioxidant and obscured functions, which can meet the multiple needs of high -speed flight wing rudder structure materials, and overcomes the high temperature mechanics and antioxidant and obscured performance of the existing ceramic -based composite materials. Insufficient issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005114578200000111
    Figure BDA0005114578200000111
Patent Text Reader

Abstract

The invention relates to a multi-element ultrahigh-temperature ceramic and C / C structure function integrated gradient composite material and a preparation method thereof.The preparation method of the multi-element ultrahigh-temperature ceramic and C / C structure function integrated gradient composite material comprises the steps that a pyrolytic carbon interface layer is deposited on the fiber surface of a carbon fiber preform through a chemical vapor deposition method, and a low-density C / C base material is obtained; the density of the carbon fiber preform is gradually increased from the surface to the inside; and performing multi-element ultra-high-temperature ceramic matrix densification on the low-density C / C base material to obtain the multi-element ultra-high-temperature ceramic and C / C structure function integrated gradient composite material. According to the preparation method provided by the invention, the integrated preparation of the structure bearing function and the anti-ablation function of the ceramic-based composite material can be realized, and the prepared multi-element ultra-high-temperature ceramic and C / C structure function integrated gradient composite material has the advantages of light weight, good bearing capacity and anti-oxidation ablation function; and multiple requirements of light weight, high structural bearing and oxidation ablation resistance of structural materials such as wings and rudders of high-speed aircrafts can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of ultra-high temperature ceramic-based composite materials, and in particular relates to a multi-element ultra-high temperature ceramic and C / C structural functional integrated gradient composite material and a preparation method thereof. Background Art

[0002] When a high-speed aircraft flies in the atmosphere for a long time, the front edge of the rudder faces a harsh service environment, with its radiation equilibrium temperature reaching over 2000°C and bearing loads of tens or even hundreds of kN. Therefore, the rudder component materials of high-speed aircraft need to have functions such as light weight, high structural load-bearing capacity, and anti-oxidation and ablation. However, existing ceramic-based composite materials are difficult to balance good high-temperature mechanics and anti-oxidation and ablation resistance, and do not have the integrated functions of structural load-bearing and anti-ablation. Summary of the invention

[0003] In response to one or more technical problems existing in the prior art, the present invention provides a multi-component ultra-high temperature ceramic and C / C structural functional integrated gradient composite material and a preparation method thereof. The preparation method provided by the present invention can realize the integrated preparation of the structural load-bearing and anti-ablation functions of the ceramic-based composite material. The prepared multi-component ultra-high temperature ceramic and C / C structural functional integrated gradient composite material has light weight, good load-bearing capacity and anti-oxidation and ablation functions, and can meet the multiple requirements of lightweight, high structural load-bearing and anti-oxidation and ablation of high-speed aircraft wing and rudder structural materials.

[0004] In a first aspect, the present invention provides a method for preparing a multi-element ultra-high temperature ceramic and C / C structural functional integrated gradient composite material, the preparation method comprising:

[0005] S1. Depositing a pyrolytic carbon interface layer on the fiber surface of a carbon fiber preform by chemical vapor deposition to obtain a low-density C / C substrate; wherein the density of the carbon fiber preform increases from the surface to the inside;

[0006] S2. Densify the low-density C / C substrate into a multi-element ultra-high temperature ceramic matrix to obtain a multi-element ultra-high temperature ceramic and C / C structural and functional integrated gradient composite material.

[0007] Preferably, the surface density of the carbon fiber preform is 0.30 to 0.35 g / cm 3 ;

[0008] The maximum density inside the carbon fiber preform is 0.60-0.65 g / cm 3 ; and / or

[0009] The carbon fiber preform has a density increasing gradient from the surface to the interior of 0.05 to 0.1 g / cm 3 .

[0010] Preferably, before depositing the pyrolytic carbon interface layer on the fiber surface of the carbon fiber preform, the carbon fiber preform is subjected to high temperature treatment; preferably, the high temperature heat treatment temperature is 1000-1800° C., and the time is 2.0-3.0 hours;

[0011] The chemical vapor deposition method uses propylene as a carbon source and nitrogen as a carrier, and deposits at 800-1100° C.; and / or

[0012] The density increment of the low-density C / C substrate and the carbon fiber preform is 60-100%.

[0013] Preferably, densifying the low-density C / C substrate into a multi-element ultra-high temperature ceramic matrix comprises:

[0014] (i) using a phenolic resin to perform 1 to 3 rounds of first impregnation, first curing and first cracking on the low-density C / C substrate until the density increment of the low-density C / C substrate meets the requirements, thereby obtaining a porous C / C intermediate;

[0015] (ii) using an alloy infiltrant to perform reactive infiltration on the porous C / C intermediate to obtain a multi-element ultra-high temperature ceramic and C / C structural and functional integrated gradient composite material.

[0016] Preferably, the first impregnation includes a first vacuum impregnation and a first pressure impregnation performed sequentially; preferably, the vacuum degree of the first vacuum impregnation is -0.15 to -0.08 MPa, the temperature of the first vacuum impregnation is room temperature, and the time of the first vacuum impregnation is 0.5 to 2.0 h; preferably, the pressure of the first pressure impregnation is 0.5 to 2.0 MPa, the temperature of the first pressure impregnation is room temperature, and the time of the first pressure impregnation is 0.5 to 2.0 h;

[0017] The temperature of the first curing is 100 to 350° C., the pressure of the first curing is 0.5 to 2.5 MPa, and the time of the first curing is 0.5 to 2.0 h;

[0018] The temperature of the first cracking is 700-1000° C., and the time of the first cracking is 2.0-4.0 h; and / or

[0019] The temperature of the reaction infiltration is 1600-1800° C., and the time of the reaction infiltration is 1.0-2.0 h.

[0020] Preferably, until the density increment of the low-density C / C substrate meets the requirement: until the density increment of the porous C / C intermediate obtained after the n-th round of first impregnation, first curing and first cracking is 20-50% compared with the low-density C / C substrate before the first impregnation, first curing and first cracking; and / or

[0021] The alloy infiltrant is one of a silicon-zirconium binary alloy and a silicon-hafnium binary alloy; preferably, the atomic weight fraction of zirconium in the silicon-zirconium alloy is 15-25%; the atomic weight fraction of hafnium in the silicon-hafnium alloy is 15-31%; more preferably, the particle size of the alloy infiltrant is 1-10 μm.

[0022] Preferably, densifying the low-density C / C substrate into a multi-element ultra-high temperature ceramic matrix comprises:

[0023] The low-density C / C substrate is subjected to multiple rounds of second impregnation, second curing and second cracking with a ceramic precursor solution until the weight gain of the obtained ceramic-based composite material meets the requirements, thereby obtaining a multi-element ultra-high temperature ceramic and C / C structural functional integrated gradient composite material; the ceramic precursor solution is at least one of a hafnium-silicon integrated ceramic precursor solution and a zirconium-silicon integrated ceramic precursor solution.

[0024] Preferably, until the weight gain of the obtained ceramic-based composite material meets the requirement: until the weight gain of the ceramic-based composite material after the nth round of second impregnation, second curing and second pyrolysis is less than 0.5% compared with the ceramic-based composite material after the n-1th round of second impregnation, second curing and second pyrolysis;

[0025] The hafnium-silicon integrated ceramic precursor solution comprises polyhafnium carbeta, polycarbosilane and phenolic resin; preferably, the molar ratio of polyhafnium carbeta, polycarbosilane and phenolic resin is 1:0.25-4:2-6; and / or

[0026] The zirconium-silicon integrated ceramic precursor solution comprises polyzirconoxane, polycarbosilane and phenolic resin; preferably, the molar ratio of polyzirconoxane, polycarbosilane and phenolic resin is 1:0.25-4:2-6.

[0027] Preferably, the second impregnation includes a second vacuum impregnation and a second pressure impregnation performed sequentially; preferably, the vacuum degree of the second vacuum impregnation is -0.15 to -0.08 MPa, the temperature of the second vacuum impregnation is room temperature, and the time of the second vacuum impregnation is 0.5 to 2.0 h; preferably, the pressure of the second pressure impregnation is 0.5 to 2.0 MPa, the temperature of the second vacuum impregnation is room temperature, and the time of the second vacuum impregnation is 0.5 to 2.0 h;

[0028] The temperature of the second curing is 100 to 350° C., the pressure of the second curing is 0.5 to 2.5 MPa, and the time of the second curing is 0.5 to 2.0 h; and / or

[0029] The temperature of the second cracking is 1200-1800° C., and the time of the second cracking is 2.0-4.0 hours.

[0030] In a second aspect, the present invention provides a multi-element ultra-high temperature ceramic and C / C structural functional integrated gradient composite material, which is prepared by the preparation method described in the first aspect.

[0031] Compared with the prior art, the present invention has at least the following beneficial effects:

[0032] The present invention first selects a carbon fiber preform whose density increases from the surface to the inside (a carbon fiber preform with a gradient structure with increasing density) and deposits a pyrolytic carbon interface layer on the surface of the carbon fiber to form a low-density C / C substrate with a gradient structure. The low-density C / C substrate is then densified to form a ceramic matrix that also has a gradient structure. The prepared composite material has a high internal carbon fiber volume fraction and good load-bearing capacity. The composite material has a high surface ceramic matrix content and good anti-oxidation and ablation function.

[0033] The preparation method provided by the present invention can realize the integrated preparation of ceramic-based composite material structural load-bearing and anti-ablation functions. The prepared multi-element ultra-high temperature ceramic and C / C structural function integrated gradient composite material has light weight, good load-bearing capacity and anti-oxidation and ablation functions, which can meet the multiple needs of lightweight, high structural load-bearing and anti-oxidation and ablation of high-speed aircraft wing and rudder structural materials, and overcome the problem that existing ceramic-based composite materials are difficult to take into account both good high-temperature mechanics and anti-oxidation and ablation resistance. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In the description of the embodiments of the present invention, unless otherwise clearly specified and limited, the terms "first", "second", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0035] In a first aspect, the present invention provides a method for preparing a multi-element ultra-high temperature ceramic and C / C structural functional integrated gradient composite material, the preparation method comprising:

[0036] S1. Depositing a pyrolytic carbon interface layer on the fiber surface of a carbon fiber preform by chemical vapor deposition to obtain a low-density C / C substrate; wherein the density of the carbon fiber preform increases from the surface to the inside;

[0037] S2. Densify the low-density C / C substrate into a multi-element ultra-high temperature ceramic matrix to obtain a multi-element ultra-high temperature ceramic and C / C structural and functional integrated gradient composite material.

[0038] The present invention first selects a carbon fiber preform whose density increases from the surface to the inside (a carbon fiber preform with a gradient structure with increasing density), and deposits a pyrolytic carbon interface layer on the fiber surface to form a low-density C / C substrate with a gradient structure. The low-density C / C substrate is then densified to form a ceramic matrix, and the ceramic matrix also has a gradient structure. The prepared composite material has a high internal carbon fiber volume fraction and good load-bearing capacity; the surface ceramic matrix content of the composite material is high, and it has good anti-oxidation and ablation function.

[0039] The preparation method provided by the present invention can realize the integrated preparation of ceramic-based composite materials with structural load-bearing and anti-ablation functions. The prepared multi-element ultra-high temperature ceramic and C / C structural function integrated gradient composite material has light weight, good load-bearing capacity and anti-oxidation and ablation functions, which can meet the multiple requirements of lightweight, high structural load-bearing and anti-oxidation and ablation of wing and rudder structural materials of high-speed aircraft, and overcomes the problem that existing ceramic-based composite materials are difficult to take into account both good high-temperature mechanics and anti-oxidation and ablation resistance.

[0040] According to some preferred embodiments, the surface density of the carbon fiber preform is 0.30 to 0.35 g / cm 3 (For example, it can be 0.30 g / cm 3 , 0.31g / cm 3 , 0.32g / cm 3 , 0.33g / cm 3 , 0.34g / cm 3 or 0.35g / cm 3 );

[0041] The maximum density inside the carbon fiber preform is 0.60-0.65 g / cm 3 (For example, it can be 0.60g / cm 3 、0.61g / cm 3 , 0.62g / cm 3 , 0.63g / cm 3 , 0.64g / cm 3 or 0.65g / cm 3 ); and / or

[0042] The carbon fiber preform has a density increasing gradient from the surface to the interior of 0.05 to 0.1 g / cm 3 (For example, it can be 0.05g / cm 3 , 0.06g / cm 3 , 0.07g / cm 3 , 0.08g / cm 3 , 0.09g / cm 3 or 0.1g / cm3 ). It should be noted that the increasing gradient of density refers to the difference between adjacent density values ​​from the surface to the inside of the carbon fiber preform.

[0043] According to some preferred embodiments, before depositing the pyrolytic carbon interface layer on the fiber surface of the carbon fiber preform, the carbon fiber preform is also subjected to high temperature treatment; preferably, the high temperature heat treatment temperature is 1000-1800°C (for example, it can be 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C or 1800°C), and the time is 2.0-3.0h (for example, it can be 2.0h, 2.2h, 2.4h, 2.6h, 2.8h or 3.0h);

[0044] The chemical vapor deposition method uses propylene as a carbon source and nitrogen as a carrier, and deposits at 800-1100° C. (for example, 800° C., 850° C., 900° C., 950° C., 1000° C., 1050° C. or 1100° C.); and / or

[0045] The density increment of the low-density C / C substrate and the carbon fiber preform is 60-100% (for example, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%).

[0046] According to some preferred embodiments, densifying the low-density C / C substrate into a multi-element ultra-high temperature ceramic matrix comprises:

[0047] (i) using a phenolic resin to perform 1 to 3 rounds of first impregnation, first curing and first cracking on the low-density C / C substrate until the density increment of the low-density C / C substrate meets the requirements, thereby obtaining a porous C / C intermediate;

[0048] (ii) using an alloy infiltrant to perform reactive infiltration on the porous C / C intermediate to obtain a multi-element ultra-high temperature ceramic and C / C structural and functional integrated gradient composite material.

[0049] According to some preferred embodiments, the first impregnation includes a first vacuum impregnation and a first pressure impregnation performed sequentially; preferably, the vacuum degree of the first vacuum impregnation is -0.15 to -0.08 MPa, the temperature of the first vacuum impregnation is room temperature, and the time of the first vacuum impregnation is 0.5 to 2.0 h; preferably, the pressure of the first pressure impregnation is 0.5 to 2.0 MPa, the temperature of the first pressure impregnation is room temperature, and the time of the first pressure impregnation is 0.5 to 2.0 h;

[0050] The temperature of the first curing is 100 to 350° C. (for example, 100° C., 150° C., 200° C., 250° C., 300° C. or 350° C.), the pressure of the first curing is 0.5 to 2.5 MPa, and the time of the first curing is 0.5 to 2.0 h;

[0051] The temperature of the first cracking is 700-1000° C. (for example, 700° C., 750° C., 800° C., 850° C., 900° C., 950° C. or 1000° C.), and the time of the first cracking is 2.0-4.0 h; and / or

[0052] The temperature of the reaction infiltration is 1600-1800° C. (for example, 1600° C., 1650° C., 1700° C., 1750° C. or 1800° C.), and the time of the reaction infiltration is 1.0-2.0 h.

[0053] According to some preferred embodiments, until the density increment of the low-density C / C substrate meets the requirement: until the density increment of the porous C / C intermediate obtained after the n-th round of first impregnation, first solidification and first cracking is 20-50% (for example, 20%, 25%, 30%, 35%, 40%, 45% or 50%) compared with the low-density C / C substrate before the first impregnation, first solidification and first cracking; and / or

[0054] The alloying agent is one of a silicon-zirconium binary alloy and a silicon-hafnium binary alloy; preferably, the atomic weight fraction of zirconium in the silicon-zirconium alloy is 15-25% (for example, it can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%); the atomic weight fraction of hafnium in the silicon-hafnium alloy is 15-31% (for example, it can be 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30% or 31%); more preferably, the particle size of the alloying agent is 1-10 μm.

[0055] According to some preferred embodiments, densifying the low-density C / C substrate into a multi-element ultra-high temperature ceramic matrix comprises:

[0056] The low-density C / C substrate is subjected to multiple rounds of second impregnation, second curing and second cracking with a ceramic precursor solution until the weight gain of the obtained ceramic-based composite material meets the requirements, thereby obtaining a multi-element ultra-high temperature ceramic and C / C structural functional integrated gradient composite material; the ceramic precursor solution is at least one of a hafnium-silicon integrated ceramic precursor solution and a zirconium-silicon integrated ceramic precursor solution.

[0057] According to some preferred embodiments, the weight gain of the obtained ceramic-based composite material meets the requirement that the weight gain of the ceramic-based composite material after the nth round of second impregnation, second curing and second cracking is less than 0.5% compared with the ceramic-based composite material after the n-1th round of second impregnation, second curing and second cracking.

[0058] According to some preferred embodiments, the hafnium-silicon integrated ceramic precursor solution includes polyhafnium carbeta, polycarbosilane and phenolic resin; preferably, the molar ratio of polyhafnium carbeta, polycarbosilane and phenolic resin is 1:0.25-4:2-6.

[0059] According to some preferred embodiments, the zirconium-silicon integrated ceramic precursor solution includes polyzirconoxane, polycarbosilane and phenolic resin; preferably, the molar ratio of polyzirconoxane, polycarbosilane and phenolic resin is 1:0.25-4:2-6.

[0060] According to some preferred embodiments, the second impregnation includes a second vacuum impregnation and a second pressure impregnation performed sequentially; preferably, the vacuum degree of the second vacuum impregnation is -0.15 to -0.08 MPa, the temperature of the second vacuum impregnation is room temperature, and the time of the second vacuum impregnation is 0.5 to 2.0 h; preferably, the pressure of the second pressure impregnation is 0.5 to 2.0 MPa, the temperature of the second vacuum impregnation is room temperature, and the time of the second vacuum impregnation is 0.5 to 2.0 h.

[0061] According to some preferred embodiments, the temperature of the second curing is 100-350°C (for example, 100°C, 150°C, 200°C, 250°C, 300°C or 350°C), the pressure of the second curing is 0.5-2.5 MPa, and the time of the second curing is 0.5-2.0 h.

[0062] According to some preferred embodiments, the temperature of the second cracking is 1200-1800°C (for example, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C or 1800°C), and the time of the second cracking is 2.0-4.0h.

[0063] In a second aspect, the present invention provides a multi-element ultra-high temperature ceramic and C / C structural functional integrated gradient composite material, which is prepared by the preparation method described in the first aspect.

[0064] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described below in conjunction with the examples. The present invention does not specifically limit the sources of the reagents used in the examples and comparative examples, and the reagents can be directly purchased or synthesized by themselves.

[0065] Example 1

[0066] By adjusting the fiber distribution of the carbon fiber preform, the density of the carbon fiber preform gradually increases from the surface to the inside. The surface density of the carbon fiber preform is 0.35g / cm 3 The inner density of the carbon fiber preform is 0.65g / cm 3 The density gradient is 0.1 g / cm 3 After the carbon fiber preform was heat treated at 1600°C for 2.0h, a pyrolytic carbon interface layer was deposited on the fiber surface of the carbon fiber preform by chemical vapor deposition (CVI) process with propylene as carbon source and nitrogen as carrier gas at a deposition temperature of 1000°C to obtain a low-density C / C substrate (the density increment of the low-density C / C substrate was 95% compared with the carbon fiber preform). Then, a precursor impregnation and pyrolysis (PIP) process is used to prepare a porous C / C intermediate. Phenolic resin is used as a precursor to sequentially perform vacuum impregnation (the vacuum degree of vacuum impregnation is -0.1 MPa, the temperature of vacuum impregnation is room temperature, and the time of vacuum impregnation is 1.5 h), pressure impregnation (the pressure of pressure impregnation is 2.0 MPa, the temperature of pressure impregnation is room temperature, and the time of pressure impregnation is 1.5 h), curing (the curing temperature is 240°C, the curing pressure is 1.5 MPa, and the curing time is 2.0 h) and pyrolysis (the pyrolysis temperature is 800°C, and the pyrolysis time is 2.0 h) on the low-density C / C substrate to obtain a porous C / C intermediate (the density increase of the porous C / C intermediate is 40% compared with the low-density C / C substrate).

[0067] A silicon-zirconium alloy infiltrant (the atomic weight fraction of zirconium in the silicon-zirconium alloy infiltrant is 18%, and the particle size of the silicon-hafnium alloy infiltrant powder is 3-8 μm) is used to carry out reactive infiltration (the reactive infiltration temperature is 1800°C and the time is 1.5 h) in a porous C / C intermediate to in situ generate a multi-component ultra-high temperature ceramic matrix, thereby obtaining a multi-component ultra-high temperature ceramic and C / C structural and functional integrated gradient composite material.

[0068] Example 2

[0069] By adjusting the fiber distribution of the carbon fiber preform, the density of the carbon fiber preform gradually increases from the surface to the inside. The surface density of the carbon fiber preform is 0.35g / cm 3 The inner density of the carbon fiber preform is 0.65g / cm 3 The density gradient is 0.05 g / cm 3After the carbon fiber preform was heat treated at 1600°C for 2.0h, a pyrolytic carbon interface layer was deposited on the fiber surface of the carbon fiber preform by chemical vapor deposition (CVI) process with propylene as carbon source and nitrogen as carrier gas at a deposition temperature of 1000°C to obtain a low-density C / C substrate (the density increment of the low-density C / C substrate was 95% compared with the carbon fiber preform); then a porous C / C intermediate was prepared by a precursor impregnation pyrolysis (PIP) process, and the low-density C / C substrate was vacuum impregnated with phenolic resin as a precursor (vacuum impregnation The vacuum degree is -0.1MPa, the temperature of vacuum impregnation is room temperature, and the time of vacuum impregnation is 1.5h) and pressure impregnation (the pressure of pressure impregnation is 2.0MPa, the temperature of pressure impregnation is room temperature, and the time of pressure impregnation is 1.5h), curing (the curing temperature is 240℃, the curing pressure is 1.5MPa, and the curing time is 2.0h) and pyrolysis (the pyrolysis temperature is 800℃, and the pyrolysis time is 2.0h) to obtain a porous C / C intermediate (the density increase of the porous C / C intermediate compared with the low-density C / C substrate is 35%).

[0070] A multi-component ultra-high temperature ceramic matrix is ​​generated in situ by using a silicon-hafnium alloy infiltrant (the atomic weight fraction of hafnium in the silicon-hafnium alloy infiltrant is 19% and the particle size of the silicon-hafnium alloy infiltrant powder is 3-8 μm) to react and melt infiltrate the porous C / C intermediate (the reaction infiltration temperature is 1750°C and the time is 1.5 h) to obtain a multi-component ultra-high temperature ceramic and C / C structural and functional integrated gradient composite material.

[0071] Example 3

[0072] By adjusting the fiber distribution of the carbon fiber preform, the density of the carbon fiber preform gradually increases from the surface to the inside. The surface density of the carbon fiber preform is 0.35g / cm 3 The inner density of the carbon fiber preform is 0.65g / cm 3 The density gradient is 0.1 g / cm 3 After the carbon fiber preform was heat treated at 1600°C for 2.0h, a pyrolytic carbon interface layer was deposited on the fiber surface of the carbon fiber preform by chemical vapor deposition (CVI) process with propylene as carbon source and nitrogen as carrier gas at a deposition temperature of 1000°C to obtain a low-density C / C substrate (the density increment of the low-density C / C substrate was 80% compared with the carbon fiber preform).

[0073] A hafnium-silicon integrated ceramic precursor solution (including polyhafnium carbene, polycarbosilane and phenolic resin in a molar ratio of 1:1:4) was used to perform 15 rounds of vacuum impregnation (the vacuum degree of vacuum impregnation was -0.10 MPa, the temperature of vacuum impregnation was room temperature, and the time of vacuum impregnation was 1.0 h), pressure impregnation (the pressure of pressure impregnation was 1.5 MPa, the temperature of pressure impregnation was room temperature, and the time of pressure impregnation was 1.0 h), curing (curing temperature was 200°C, curing pressure was 1.5 MPa, and curing time was 1.0 h), and high-temperature pyrolysis (pyrolysis temperature was 1500°C, and pyrolysis time was 2.0 h) on a low-density C / C substrate to obtain a multi-element ultra-high temperature ceramic and C / C structural functional integrated gradient composite material.

[0074] Example 4

[0075] By adjusting the fiber distribution of the carbon fiber preform, the density of the carbon fiber preform gradually increases from the surface to the inside. The surface density of the carbon fiber preform is 0.35g / cm 3 The inner density of the carbon fiber preform is 0.65g / cm 3 The density gradient is 0.05 g / cm 3 After the carbon fiber preform was heat treated at 1600°C for 2.0h, a pyrolytic carbon interface layer was deposited on the fiber surface of the carbon fiber preform by chemical vapor deposition (CVI) process with propylene as carbon source and nitrogen as carrier gas at a deposition temperature of 1000°C to obtain a low-density C / C substrate (the density increment of the low-density C / C substrate was 85% compared with the carbon fiber preform).

[0076] A zirconium-silicon integrated ceramic precursor solution (including polyzirconium carbene, polycarbosilane and phenolic resin in a molar ratio of 1:1:4) was used to carry out 15 rounds of vacuum impregnation (the vacuum degree of vacuum impregnation was -0.10 MPa, the temperature of vacuum impregnation was room temperature, and the time of vacuum impregnation was 1.0 h), pressure impregnation (the pressure of pressure impregnation was 1.5 MPa, the temperature of pressure impregnation was room temperature, and the time of pressure impregnation was 1.0 h), curing (curing temperature was 200°C, curing pressure was 1.5 MPa, and curing time was 1.0 h), and high-temperature pyrolysis (pyrolysis temperature was 1600°C, and pyrolysis time was 2.0 h) on a low-density C / C substrate to obtain a multi-element ultra-high temperature ceramic and C / C structural functional integrated gradient composite material.

[0077] Comparative Example 1

[0078] The carbon fiber preform is basically the same as Example 2, except that the carbon fiber preform is a common carbon fiber preform without density gradient, and the density of the carbon fiber preform is 0.6 g / cm 3 .

[0079] Comparative Example 2

[0080] The same as Example 3, except that the carbon fiber preform is a common carbon fiber preform without density gradient, and the density of the carbon fiber preform is 0.6 g / cm 3 .

[0081] The performance testing methods of the composite materials prepared in the examples and comparative examples of the present invention are as follows, and the relevant performance data are shown in Table 1.

[0082] Mechanical properties

[0083] Room temperature tensile strength test: GJB / 8736-2015 continuous fiber reinforced ceramic matrix composite material room temperature tensile performance test method is adopted.

[0084] Room temperature flexural strength test: Q / SB 513-2013 continuous fiber reinforced ceramic matrix composite room temperature flexural performance test method is used.

[0085] Anti-oxidation and ablation performance

[0086] The oxyacetylene ablation test adopted the GJB 323B-2018 ablation material ablation test method. During the test, the ablation surface temperature of the test sample was 2000°C.

[0087] Table 1. Performance data of composite materials obtained from the examples of the present invention and comparative examples

[0088]

[0089] It should be noted that since Comparative Examples 1 and 2 use fiber preforms without density gradient, the resulting composite materials also do not have density gradient. The “-” in Table 1 indicates that the performance of each part of the composite material is similar, without distinguishing between the surface and the interior.

[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a multi-element ultra-high temperature ceramic and C / C structural functional integrated gradient composite material, characterized in that: The preparation method comprises: S1. Depositing a pyrolytic carbon interface layer on the fiber surface of a carbon fiber preform by chemical vapor deposition to obtain a low-density C / C substrate; wherein the density of the carbon fiber preform increases from the surface to the inside; S2. Densify the low-density C / C substrate into a multi-element ultra-high temperature ceramic matrix to obtain a multi-element ultra-high temperature ceramic and C / C structural and functional integrated gradient composite material.

2. The preparation method according to claim 1, characterized in that: The surface density of the carbon fiber preform is 0.30 to 0.35 g / cm 3 ; The maximum density inside the carbon fiber preform is 0.60-0.65 g / cm 3 ; and / or The carbon fiber preform has a density increasing gradient from the surface to the interior of 0.05 to 0.1 g / cm 3 .

3. The preparation method according to claim 1, characterized in that: Before depositing the pyrolytic carbon interface layer on the fiber surface of the carbon fiber preform, the carbon fiber preform is subjected to high temperature treatment; preferably, the high temperature heat treatment temperature is 1000-1800° C. and the time is 2.0-3.0 hours; The chemical vapor deposition method uses propylene as a carbon source and nitrogen as a carrier, and deposits at 800-1100° C.; and / or The density increment of the low-density C / C substrate and the carbon fiber preform is 60-100%.

4. The preparation method according to claim 1, characterized in that: Densifying the low-density C / C substrate into a multi-element ultra-high temperature ceramic matrix comprises: (i) using a phenolic resin to perform 1 to 3 rounds of first impregnation, first curing and first cracking on the low-density C / C substrate until the density increment of the low-density C / C substrate meets the requirements, thereby obtaining a porous C / C intermediate; (ii) using an alloy infiltrant to perform reactive infiltration on the porous C / C intermediate to obtain a multi-element ultra-high temperature ceramic and C / C structural and functional integrated gradient composite material.

5. The preparation method according to claim 4, characterized in that: The first impregnation includes a first vacuum impregnation and a first pressure impregnation performed sequentially; preferably, the vacuum degree of the first vacuum impregnation is -0.15 to -0.08 MPa, the temperature of the first vacuum impregnation is room temperature, and the time of the first vacuum impregnation is 0.5 to 2.0 h; preferably, the pressure of the first pressure impregnation is 0.5 to 2.0 MPa, the temperature of the first pressure impregnation is room temperature, and the time of the first pressure impregnation is 0.5 to 2.0 h; The temperature of the first curing is 100 to 350° C., the pressure of the first curing is 0.5 to 2.5 MPa, and the time of the first curing is 0.5 to 2.0 h; The temperature of the first cracking is 700-1000° C., and the time of the first cracking is 2.0-4.0 h; and / or The temperature of the reaction infiltration is 1600-1800° C., and the time of the reaction infiltration is 1.0-2.0 h.

6. The preparation method according to claim 4, characterized in that: Until the density increment of the low-density C / C substrate meets the requirement that the density increment of the porous C / C intermediate obtained after the n-th round of first impregnation, first solidification and first cracking is 20-50% compared with the low-density C / C substrate before the first impregnation, first solidification and first cracking; and / or The alloy infiltrant is one of a silicon-zirconium binary alloy and a silicon-hafnium binary alloy; preferably, the atomic weight fraction of zirconium in the silicon-zirconium alloy is 15-25%; the atomic weight fraction of hafnium in the silicon-hafnium alloy is 15-31%; more preferably, the particle size of the alloy infiltrant is 1-10 μm.

7. The preparation method according to claim 1, characterized in that: Densifying the low-density C / C substrate into a multi-element ultra-high temperature ceramic matrix comprises: The low-density C / C substrate is subjected to multiple rounds of second impregnation, second curing and second cracking with a ceramic precursor solution until the weight gain of the obtained ceramic-based composite material meets the requirements, thereby obtaining a multi-element ultra-high temperature ceramic and C / C structural functional integrated gradient composite material; the ceramic precursor solution is at least one of a hafnium-silicon integrated ceramic precursor solution and a zirconium-silicon integrated ceramic precursor solution.

8. The preparation method according to claim 7, characterized in that: Until the weight gain of the obtained ceramic matrix composite material meets the requirement that the weight gain of the ceramic matrix composite material after the nth round of second impregnation, second curing and second pyrolysis is less than 0.5% compared with the ceramic matrix composite material after the n-1th round of second impregnation, second curing and second pyrolysis; The hafnium-silicon integrated ceramic precursor solution comprises polyhafnium carbeta, polycarbosilane and phenolic resin; preferably, the molar ratio of polyhafnium carbeta, polycarbosilane and phenolic resin is 1:0.25-4:2-6; and / or The zirconium-silicon integrated ceramic precursor solution comprises polyzirconoxane, polycarbosilane and phenolic resin; preferably, the molar ratio of polyzirconoxane, polycarbosilane and phenolic resin is 1:0.25-4:2-6.

9. The preparation method according to claim 7, characterized in that: The second impregnation includes a second vacuum impregnation and a second pressure impregnation performed sequentially; preferably, the vacuum degree of the second vacuum impregnation is -0.15 to -0.08 MPa, the temperature of the second vacuum impregnation is room temperature, and the time of the second vacuum impregnation is 0.5 to 2.0 h; preferably, the pressure of the second pressure impregnation is 0.5 to 2.0 MPa, the temperature of the second vacuum impregnation is room temperature, and the time of the second vacuum impregnation is 0.5 to 2.0 h; The temperature of the second curing is 100 to 350° C., the pressure of the second curing is 0.5 to 2.5 MPa, and the time of the second curing is 0.5 to 2.0 h; and / or The temperature of the second cracking is 1200-1800° C., and the time of the second cracking is 2.0-4.0 hours.

10. A multi-element ultra-high temperature ceramic and C / C structural functional integrated gradient composite material, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • C / HfC-ZrC-SiC ultrahigh temperature ceramic matrix composite material and preparation method thereof

    CN112592194A

  • Carbon-ceramic hybrid matrix gradient structure composite material and preparation method thereof

    CN115611645A

  • Gradient ultrahigh-temperature ceramic-based composite material and preparation method thereof

    CN117756554A

  • Oxidation-ablation-resistant heat-conducting ceramic-based composite material and preparation method thereof

    CN117923923A

  • Preparation method of micro-area in-situ reaction of ceramic-based composite material reinforced with high strength fibre

    WO2013060175A1